Informational inclusion: A challenge for creative cities: Un análisis de las desigualdades en el acceso a la información y sus implicaaciones para el desarrollo urbano - Orella Peinado, Nekane (Street Art & Urban Creativity, 2025)
This research aims to analyze the barriers that people with intellectual disabilities face in accessing information in an increasingly digitalized environment and how these limitations affect their social participation and ability to exercise their rights as citizens. Based on the hypothesis that people with intellectual disabilities experience significant difficulties in understanding and using available information, this study seeks to identify the main barriers and propose strategies to overcome them, in order to promote informational inclusion in creative cities.